Design-based research in education : theory and applications - Philippakos, Zoi A.; Howell, Emily; Pellegrino, Anthony; Reinking, David (The Guilford Press, 2021)
"Effective research in educational settings requires collaboration between researchers and school-based practitioners to codesign instruction and assessment, analyze findings to inform subsequent iterations, and make thoughtful revisions. This innovative reference and course text examines the theory and practice of design-based research (DBR), an important methodology for conducting studies in authentic educational contexts. Across 13 chapters, leading experts provide specific examples of high-quality DBR addressing different research foci, grade levels, and subject areas (literacy/English language arts, math, and science). Applications are presented for curriculum development, intervention, assessment, and digital contexts, as well as teaching second-language learners. Also addressed is DBR's role in educator preparation, professional development, dissertation research, and technical education"- Resumé vydavatel
Keywords: pedagogický výzkum -- metodologie; kurikulum; educational research -- methodology; curriculum; sborníky; papers of several authors